IMPLEMENTASI REWARD TERHADAP MOTIVASI BELAJAR SISWA KELAS II SD ISLAM ASYSYAKIRIN KOTA TANGERANG - Fitria Utami, Angelia; Eka Saputri, Rahmawati; Sa'odah, Sa'odah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The lack of enthusiasm and active participation among students in learning activities is a common challenge in elementary education, including in the second-grade class at SD Islam Asysyakirin, Tangerang City. This study aims to describe the implementation of rewards in enhancing students' learning motivation. A descriptive qualitative approach was used, involving 21 participants consisting of 10 second-grade students, 10 parents, and 1 homeroom teacher. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The findings show that the types of rewards given by the teacher include verbal rewards (praise such as